Development and implementation of hardware and software for a minicomputer based programmable interval timer for use in point process analysis of neuronal action potentials - Willenberg, Keith David (Division of Biomedical Engineering, 2018)
A precision programmable interval timer (PIT) for use in point process analysis of the neutronal action potentials derived from multiple extracellular electrode arrays is described. The PIT is based on a commercially available LSI package, INS8253 and is interfaced to a Data General (DG) microNova 16-bit microcomputer via a DG General Purpose Interface (GPI) board. The programmable clock periods range from 1 μsec to 10 msec in decade multiples, offering a total timing duration of 65 msec to 650 sec. The PIT operates in two Modes : 1. Count-down timer 2. Elapsed time timer (Event resettable timer) Clock-overrun and data lost flags are provided. Testing and applications software have also been developed.